Taylor and Vattimo on the place of culture in political practical reasoning - Saiz, Mauro Javier (2023)
Fil: Saiz, Mauro Javier. Pontificia Universidad Católica Argentina. Facultad de Ciencias Sociales. Instituto de Investigaciones; Argentina